Investigating the Relationship between Laboratory Information System User Satisfaction and the Quality of Laboratory Services in Saudi Arabian Hospitals: A Cross-Sectional Study - Sultan Hussain Bin Shannan Alghamdi; Nasser Mareeh M Aldhafeeri; Saud Quayman Wabri Aldhafeeri; Abdulaziz Ramadan Dughayyim Aldhafeeri; Tahani Thujayl Otaysh Aldhafeeri; Nawaf Fahad Aftan Alanazi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Laboratory information systems (LIS) play a crucial role in managing laboratory data and supporting quality laboratory services. However, limited research has explored the relationship between LIS user satisfaction and the quality of laboratory services in Saudi Arabian hospitals. This study investigated this relationship and identified factors influencing LIS user satisfaction and service quality. Methods: A cross-sectional study was conducted among 400 laboratory professionals from 15 hospitals using stratified random sampling. Data were collected using a validated questionnaire assessing LIS user satisfaction and the quality of laboratory services. Descriptive statistics, Pearson’s correlation, and multiple regression were used for analysis. Results: Participants reported moderate levels of LIS user satisfaction (M=3.5, SD=0.8) and perceived quality of laboratory services (M=3.8, SD=0.7). LIS user satisfaction was significantly correlated with service quality (r=0.65, p<0.001). Regression analysis revealed that system reliability (β=0.35, p<0.01), information quality (β=0.30, p<0.01), and technical support (β=0.20, p<0.05) were significant predictors of LIS user satisfaction, which in turn predicted service quality (β=0.60, p<0.001). Conclusion: LIS user satisfaction is significantly associated with the quality of laboratory services in Saudi Arabian hospitals. Enhancing system reliability, information quality, and technical support can improve LIS user satisfaction and subsequently elevate service quality. Investing in robust LIS and providing adequate training and support to users are recommended to optimize laboratory performance and patient care.